PARTISIPASI PESERTA DALAM PELAKSANAAN PROGRAM GEN Z TALKSHOW DI SMAN 1 BAREGBEG KABUPATEN CIAMIS - Liviyani, Leni; Suganda, Silviani; Maulida, Siti Zakiyah; Hilmadilla Praja, Dena; Trysiani, Nabila Ayu; Novitasari, Nastiti (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Community participation is an important factor in the success of program implementation. Likewise, the Gen Z Talk Show Program is designed as an interactive forum that discusses topics surrounding verbal sexual harassment in the form of catcalling that occurs in Generation Z. By holding the Gen Z Talk Show program (Resisting Verbal Sexual Harassment: Catcalling) at SMAN 1 Baregbeg, it is hoped that more increasing awareness among teenagers, especially activity participants, regarding the dangers of catcalling¸ providing education and encouraging active participation by the community, especially activity participants, to be braver. refuse and report acts of sexual harassment catcalling. In this activity we contribute as instructors and program organizers. The method for implementing this service activity uses counseling techniques using lecture, discussion and question and answer methods and using Inquiry Learning strategies. The results of the Gen Z Talk Show activities held at SMAN 1 Baregbeg had a positive impact on participants because participants were able to participate actively, including (1) Participation of participants in increasing awareness of the dangers of catcalling (2) Participation of participants in sharing catcalling experiences (3) Participation Participants Discussion on the Impact of Catcalling (4) Participation of participants in preventing catcalling.